Synthesis and Preliminary Biological Evaluations of Fluorescent or 149Promethium Labeled Trastuzumab-Polyethylenimine - Jonathan Fitzsimmons; Tapan Nayak; Cathy Cutler; Robert Atcher (Biomedicines, 2015)
Background: Radioimmunotherapy utilize a targeting antibody coupled to a therapeutic isotope to target and treat a tumor or disease. In this study we examine the synthesis and cell binding of a polymer scaffold containing a radiotherapeutic isotope and a targeting antibody. Methods: The multistep synthesis of a fluorescent or 149Promethium-labeled Trastuzumab-polyethyleneimine (PEI), Trastuzumab, or PEI is described. In vitro uptake, internalization and/or the binding affinity to the Her2/neu expressing human breast adenocarcinoma SKBr3 cells was investigated with the labeled compounds. Results: Fluorescent-labeled Trastuzumab-PEI was internalized more into cells at 2 and 18 h than fluorescent-labeled Trastuzumab or PEI. The fluorescent-labeled Trastuzumab was concentrated on the cell surface at 2 and 18 h and the labeled PEI had minimal uptake. DOTA-PEI was prepared and contained an average of 16 chelates per PEI; the compound was radio-labeled with 149Promethium and conjugated to Trastuzumab. The purified 149Pm-DOTA-PEI-Trastuzumab had a radiochemical purity of 96.7% and a specific activity of 0.118 TBq/g. The compound demonstrated a dissociation constant for the Her2/neu receptor of 20.30 ± 6.91 nM. Conclusion: The results indicate the DOTA-PEI-Trastuzumab compound has potential as a targeted therapeutic carrier, and future in vivo studies should be performed.